P158 A nurse-led model for tuberculosis services delivers safe and effective care. (11th November 2022) - Anderson, B; Fowler, L; Stott, C; Gregory, L; Ahmed, R
Abstract : Introduction: The Covid-19 pandemic led to stretched, and many suspended services throughout the NHS. Guidance was issued regarding Tuberculosis (TB) services which were deemed essential to continue. 1 We analysed how the pandemic changed TB services in a busy District General Hospital with moderate TB workload and the impact on diagnosis, follow-up, and patient outcome. Methods: Data were reviewed for TB patients diagnosed April 2018-March 2019 (pre-pandemic) and April 2020-March 2021 (mid-pandemic) at Royal Bolton Hospital. Results: See table 1 . Discussion: The pandemic led to significant changes to our service. The majority of doctor-led clinics were cancelled to cover inpatient wards. Pre-pandemic, TB Specialist-nurses (TBSNs) did some follow-up TB clinics but predominantly focussed on contact-tracing, counselling, and medication compliance. During the pandemic TBSNs were upskilled and supported to do the majority of TB clinics, managing active and latent TB patients with access to a consultant via telephone and email. There was a weekly MDT with the consultant TB lead to discuss any issues and provide support. The daily availability of ad-hoc consultant support as necessary was a crucial aspect of the nurse-led model. More patients had extra-pulmonary or multi-site TB mid-pandemic, suggesting probable increased complexity. There was less drug-resistance mid-pandemic however. TBSNs started treatment in 21% of cases, compared to 0% pre-pandemic, reflecting the new nurse-led model. Patients had a similar number of follow-up appointments. Mid-pandemic these became predominantly nurse-led. The majority of these appointments remained face-to-face despite restrictions. Despite the change in model and patient complexity, treatment was commenced at a similar interval after symptom onset. There were fewer hospital admissions mid-pandemic. Fewer patients were lost to follow-up. One TB patient died mid-pandemic while being treated for Covid-19 as an inpatient. Conclusion: A nurse-led model for TB services provides safe, effective, and timely care. An expanded TBSN role with the support of a proactive, easily-accessible consultant may present a good model for TB service provision going forward. Further research is needed to test this model outside of the pandemic context. References: British Thoracic society. Tuberculosis services during the Covid-19 pandemic. Available at https://www.brit-thoracic.org.uk/covid-19/covid-19-information-for-the-respiratory-community/